Development of religious tourism: perceptions of Christian Orthodoxy ecclesiastical communities and leaders - Liasidou, Sotiroula; Pericleous, Katerina; Garanti, Zanete (My University, 2025)
This paper aims to investigate the perceptions of ecclesiastical communities and leaders on the development of religious tourism, focusing on its potential economic and social benefits while ensuring that tourism practices align with religious doctrines to preserve the sanctity and spirituality of sacred sites.
Keywords: Religious tourism; Pilgrimage; Cyprus; Christian orthodox religion; Sacred places; Monasteries